The Mediating Role Of Psychological Empowerment On The Effect Between Person-Organization Fit And Innovative Work Behaviour - Winarsih, Putri Intan; Mulatsih, Listiana Sri; Kamener, Dahliana (Sahabat Publikasi, 2025)
This study investigates the effect among person-organization fit on the innovative work behavior and psychological empowerment as mediating in the public sector of West Pasaman, drawing on the theoretical framework of Social Exchange Theory. Data were collected from 66 individuals working in public organizations and analyzed using the SEM-PLS 3.2.9 method. The findings highlight the crucial mediating role of psychological empowerment in the relationship between person-organization fit and innovative work behavior. This study contributes to the literature by emphasizing the importance of psychological empowerment in fostering innovative work behavior. The results show that person-organization fit has a positive and significant effect on both psychological empowerment and innovative work behavior. Furthermore, psychological empowerment positively and significantly influences innovative work behavior and mediates the relationship between person-organization fit and innovative work behavior. Additionally, it provides practical implications for enhancing person-organization fit and psychological empowerment to support a culture of innovation in the public sector.